REFLECTIONS OF MOVEMENT AND HEALTH IN THE CURRENT SPORTS CULTURAL ANTHROPOLOGY - OBORNÝ, Josef; BERNHAUSEROVÁ, Andrea; BÁBELA, Michal (Advances in Social Sciences Research Journal, 2017)
The article presents a theoretical scientific study of movement, sports movement, health and spiritual health. It informs about the basic aspects of the purpose of the human movement and it drafts the range of the term spiritual health. The study is teleological heading to detection how the cultural anthropology interprets the human movement and health by the current needs of a man and by his current comprehending, and at the same time, to the presentation of the detections of cultural anthropology of sport in the area of the human sport movement. It applies methodological instruments of the qualitative research, which include logically consistent contemplation, selective teleological compilation and non-participant observation via electronic medium. From the cultural anthropological point of view, it defines the basic aspects of health: Personal aspect – express the health care as an indicator of cultural behaviour pattern of an individual. Social aspect – health is reflected as an irreplaceable social value, which is used by every individual of a given society. In a global aspect, the health is reflected as an universal value and the health care gains literally a global form, e.g. in a fight against the possible forms of a certain world pandemia. In the end, the study formulates an assignment which confronts the cultural anthropology of sport with the research of a nonreligious spirituality, which together with some other factors in a great measure configurator the quality of an existent human life.